Lions of darkness - Joubert, Dereck; Joubert, Beverly; David, Keith (Washington, D.C. : National Geographic Society, 1993)
The program shows a gripping story of a growing lion pride in Botswana. Includes an half-hour film entitled A passion for Africa
Writer, photographer, Dereck Joubert
Narrator: Keith David
Keywords: Lions